Pengaruh Motivasi Dan Pendidikan Terhadap Kinerja Guru Pondok Pesantren Yatim Piatu Baiturrahman Kabupaten Bekasi: Penelitian - Abdul Rahmaan Nurkarim; Zaharuddin; Sumardi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to examine the influence of motivation and education on teacher performance at the Baiturrahman Orphanage Islamic Boarding School in Bekasi Regency. Using a quantitative approach with an associative-causal design, this study involved the entire population of 31 teachers as the sample through a total sampling or census technique. Data was collected using a Likert scale questionnaire and documentation study, then analyzed using descriptive and inferential statistical analysis through multiple linear regression tests with the SPSS 31 program. The results indicate that: (1) Motivation has a partially positive and significant effect on teacher performance, with a tcount​ (3.487) > ttable​ (2.04523) and a significance of 0.002 < 0.05. (2) Education has a partially positive and significant effect on teacher performance, with a tcount​ (3.419) > ttable​ (2.04523) and a significance of 0.002 < 0.05. (3) Motivation and education simultaneously have a positive and significant effect on teacher performance, with an Fcount​ (20.957) > Ftable​ (3.34) and a significance of 0.001 < 0.05. The coefficient of determination (R²) of 0.600 indicates that 60% of the variation in teacher performance can be explained by motivation and education collectively, while the remaining 40% is influenced by other factors.